The Case Study of Forest Bioenergy as a Method for the Application of Stratified Random Sampling with Optimum Allocation - Tsatiris, M. N. (Current Approaches in Science and Technology Research Vol. 3, 2021)
In this paper, a methodology analysis was carried out for the application of stratified random sampling with optimum allocation in the case of a research topic involving the rural population and exhibiting high differentiations among the three strata into which this population could be classified. The rural population of Evros Prefecture (Greece) was classified into three strata based on the mean altitude of settlements for the estimation of mean consumption of forest fuelwood for covering heating and cooking needs in households in these three strata. The quantitative variable used to form strata is in the case of this study the family income that is called a factor. With this stratification we expect to have more homogeneity within the strata so that we need a smaller size of sample and the application of stratified random sampling to be more economic than the simple random sampling. The analysis of this methodology includes a) determining the total size of the sample for the entire rural population and allocating it to the various strata; b) investigating the effectiveness of stratification using the technique of analysis of variance (One-Way ANOVA); and c) going to conduct sampling research with the realization of face-to-face interviews in selected households and d) the control of forms of the questionnaire and the analysis of data by using the statistical package for social sciences, SPSS for Windows. All data for the analysis of this methodology and its practical application were collected through pilot sampling in each stratum. The review of literature did not turn up any relative papers.